Climate change literacy ability profile in junior high school students in ogan ilir regency - Anggraini, May Liza; Destiansari, Elvira; Meilinda, Meilinda (STKIP Persada Khatulistiwa Sintang, 2025)
Climate change is a global issue that requires awareness and understanding among younger generations to support sustainable environmental actions. This study aims to analyze the profile of climate change literacy among junior high school students (SMP) in Ogan Ilir Regency by considering school accreditation levels A, B, and C. The research employed a quantitative descriptive method using purposive sampling, involving 184 ninth-grade students from three schools. The instrument consisted of 40 items covering three indicators: knowledge, attitude, and competence, with Cronbach’s alpha reliability scores of 0.548, 0.900, and 0.511, respectively. Instrument validity testing showed adequate results, with a KMO value of 0.863, SRMR of 0.072, and GFI of 0.990. The findings indicate that 46% of students were in the moderate category of climate change literacy. The attitude indicator achieved the highest percentage at 48%, reflecting a good level of awareness and concern toward climate change issues. However, school accreditation does not necessarily determine literacy level, as evidenced by SMP C (Accreditation C), which recorded the highest percentage in the high category overall. These results imply the need to strengthen environmentally-based curricula and implement contextual learning approaches to enhance students’ climate change literacy.